A new dynamical mechanism of incomplete fusion in heavy-ion collisions - A.K. Nasirov; B.M. Kayumov; O.K. Ganiev; G.A. Yuldasheva (Physics Letters B, 2023)
The incomplete fusion has been proved as the emission of the α particle from the very mass-asymmetric state the dinuclear system during its evolution to complete fusion which is hindered due to the increase in the intrinsic fusion barrier related with the large rotational energy. The results of the dinuclear system model have confirmed that the incomplete fusion in heavy-ion collisions occurs at a large orbital angular momentum (L>30ħ) when the sufficient part of the initial collision energy removes as centrifugal energy.